The expected and the unexpected in the Polish language - Miodek, Jan (Papers in Linguistics, 2023)
The article concerns several selected grammatical categories in the Polish language and their evolution. The author explains that while sometimes, this evolution follows general language mechanisms, as with variants of the compound future tense, such as będę pisać – będę pisał (‘I will write’) or the accusative of the demonstrative pronoun ta: tę – tą (‘this’, referring to a feminative), other times, the process takes place in unexpected ways, as with the genitive plural of nouns ending with the consonants c, dz, cz, dż, sz, ż, rz and l, the feminine noun postać (‘form’ or ‘character’) or feminatives